Mechanical influences on endothelial cell network formation in vitro - Groothuis, A.; Wilson, C. J.; Kasper, G.; van Scherpenzeel, K. M.; Simon, P.; Bail, H. J.; Schütz, M. A.; Duda, G. N. (Osteologie, 2010)
While both the restoration of the blood supply and an appropriate local mechanical environment are critical for uneventful bone healing, their influence on each other remains unclear. Human bone fracture haematomas (< 72 h post-trauma) were cultivated for 3 days in fibrin matrices, with or without cyclic compression. Conditioned medium from these cultures enhanced the formation of vessel-like networks by HMEC-1 cells, and mechanical loading further elevated it, without affecting the cells’ metabolic activity. While haematomas released the angiogenesis-regulators, VEGF and TGF-β1, their concentrations were not affected by mechanical loading. However, direct cyclic stretching of the HMEC-1 cells decreased network formation. The appearance of the networks and a trend towards elevated VEGF under strain suggested physical disruption rather than biochemical modulation as the responsible mechanism. Thus, early fracture haematomas and their mechanical loading increase the paracrine stimulation of endothelial organisation in vitro, but direct periodic strains may disrupt or impair vessel assembly in otherwise favourable conditions.
Keywords: Angiogenesis; mechanical stimulation; haematoma